Canopy Nitrogen Addition and Soil Warming Affect Conifer Seedlings’ Phenology but Have Limited Impact on Growth and Soil N Mineralization in Boreal Forests of Eastern Canada - Marty, Charles; Piquette, Joanie; Dussault-Chouinard, Émilie; Morin, Hubert; Thiffault, Nelson; Houle, Daniel; Bradley, Robert L.; Ouimet, Rock; Simpson, Myrna J.; Paré, Maxime C. (Frontiers in Forests and Global Change, 2020)
Changes in atmospheric N deposition and the global warming associated with human activities may impact soil organic matter mineralization rate, with possible consequences on ecosystem functioning and productivity. In this study, soil temperature was increased by +2–4 °C from April to July with heating cables and artificial rain was applied above the canopy of mature stands from June to September to simulate a 50% increase in N concentration of atmospheric deposition for a period of nine years (2008–2016) in two eastern Canada boreal forests (BER and SIM). We assessed the effects of these treatments on the rate of organic N mineralization and on the growth, phenology and N sources of Abies balsamea (L.) Mill. (balsam fir; BF) and Picea mariana (Mill.) BSP (black spruce; BS) seedlings growing below the mature tree’s canopies. The soil warming (SW) treatment had no significant effect on both net and gross N mineralization rates, whereas canopy N addition (CNA) decreased gross N mineralization rate by 23% and forest floor’s alkyl/O-alkyl C ratio by ~15% as compared to unfertilized plots. This decrease likely resulted from a reduced mining activity by soil microorganisms due to increased inorganic N availability. Foliar δ15N in the control plots was markedly lower in BS than in BF and at BER than at SIM (–4.8‰ and –2.9‰ in BS at BER and SIM, respectively; 1.6‰ and 3.8‰ in BF at BER and SIM, respectively). This was interpreted as a higher contribution of 15N-depleted N derived from mycorrhizal fungi in BS and at BER, the colder and the more N-depleted site. The SW and CNA treatments had nonsignificant effects on seedling growth and foliar chemistry. In contrast, SW caused a premature bud outbreak and faster bud development for both species at both sites. Overall, our results show that increased soil temperature and N deposition in boreal forests may not impact soil fertility and vegetation growth as much as previously thought, but climate warming, by initiating earlier and faster bud development, may however expose seedlings to late spring frosts in the future.